Just like heaven eaudiobook - Quinn, Julia (Smythe-Smith Quartet, 2011)
Once again, #1 New York Times bestselling author Julia Quinn transports her readers to historical romance heaven! Quinn's Just Like Heaven is the dazzling first installment of a delightful quartet of Regency Era-set tales featuring the romantic exploits of the well-meaning but less-than-accomplished Smythe-Smith musicians—in this case, a beautiful violinist in the pitiful group who has her sights set on marrying the last unwed Bridgerton...unless her handsome, love-struck guardian has anything to say about it. Bridgerton fans will cry, "Encore!"—as will every reader who adores England's Regency period and great love stories that are smart, witty, and lighthearted.